Parasitological analysis of vegetables and assessment of care and knowledge for fresh consumption by population (Revista Brasileira Multidisciplinar, 2020)
Introduction: The large number of enteroparasite contamination is indicative of the poor hygienic-sanitary quality, and draw attention to the importance of measures aimed at informing the population. Contamination of food, especially those consumed in natura, is known to be frequent and needs attention at the time of consumption. Objective: to evaluate the presence of intestinal parasites present in samples of vegetables grown in different systems and to verify the care provided by the population for the consumption of such foods. Methods: Analysis by spontaneous sedimentation and questionnaire to evaluate the knowledge and habits of hygiene of vegetables. Results: 50 organic, conventional and hydroponic vegetables were analyzed, among species of Watercress, Lettuce, Cabbage and Arugula. Of these, 34 (68%) presented intestinal parasite contamination, being the highest frequency of hydroponic contamination, with positivity in 73.7%. The most frequent parasites were Strongyloides stercoralis, Ancylostoma sp. and Entamoeba coli. Also, the general population does not have the habit of sanitizing the vegetables in order to eliminate possible pathogens. Conclusion: The correct hygiene of vegetables is an important factor for the control of parasitoses. It is important to control and monitor the water quality  and  of the added additives during planting of vegetables.